IMPLEMENTASI KEWIRAUSAHAAN: PENGOLAHAN PRODUK HASIL PERTANIAN DI DESA KRANGGAN KECAMATAN NGAJUM KABUPATEN MALANG JAWA TIMUR - Kristina Sedyastuti (COMMENT: Journal of Community Empowerment, 2022)
Kranggan Village is one of the villages in Ngajum District, Malang Regency, East Java Province., There are still a small number of MSMEs and there are still many housewives who have unproductive time. So that this makes one of the good potentials for developing MSME entrepreneurs. Empowerment of Housewives to Improve the Family Economy, most of whom are also farmers with various agricultural products spread across the region.Basically, the purpose of implementing Community Service is to be able to provide new ideas about Entrepreneurship and to motivate housewives who are coordinated as PKK members and youths who are coordinated in the Karang Taruna group in order to open their horizons to carry out entrepreneurial activities.The target to be achieved is to become a creative community and be able to make processed products made from agricultural products such as bananas, cassava, corn, and other products to be used as an idea to become an opportunity for entrepreneurship so that it can increase family income and can use it for entrepreneurship in making food. light.The method of implementing community service is to offer counseling and training and discussions about the process of making snacks. While the implementation of community service in November 2021.The results and outputs targeted by the service are with training to make appropriate products in the form of snacks, the people who take part in the training will become entrepreneurs, especially making snacks so that they can increase their understanding and knowledge about entrepreneurship in making snacks and can improve the family economy. There are 2 mothers who have started a business, namely catering and sewing services through can be used as an example and can motivate other mothers and youth organizations, especially through SMEs using social media as a marketing tool where every training participant has a cellphone/android. Hopefully, this community service can provide new enthusiasm after experiencing the Covid-19 Pandemic and bring the Kranggan village community to be more advanced and prosperous. Meanwhile, the results of the service will also be submitted to the journal of the Community Empowerment Tehnokrat Indonesia University. Keywords: : 1,entrepreneurship,2, processed products, 3,agricultural products, 4,Kranggan Village.